1990
DOI: 10.1111/j.1365-2621.1990.tb01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Red Raspberry Juice and Wine: Effect of Processing and Storage on Anthocyanin Pigment Composition, Color and Appearance

Abstract: Red raspberry wine was made from thawed fruit by fermentation of pulp, depectinized juice, and pasteurized depectinized juice. The influences of fining and storage were also investigated. The anthocyanin pigment profiles of the samples were determined by high performance liquid chromatography (HPLC), and additional color indices by spectrophotometry and Hunter calorimetry. Anthocyanin pigments degraded mainly during fermentation, with total losses after storage of at least 50%. Cyanidin-3-glucoside was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
69
2
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 6 publications
19
69
2
2
Order By: Relevance
“…A similar reduction trend was seen as that observed for berries in frozen storage where C-3-G showed the highest reduction while the lowest reductions were noticed in peonidin 3-O-glucoside and pelargonidin 3-glucoside. This is supported by other studies that report that C-3-G is one of the most reactive ANCs during processing (Rommel et al, 1990;Boyles et al, 1993;Garcia-Viguera et al, 1998). Furthermore, Fleschhut et al (2006) reported that an increase in hydroxyl groups in the B-ring of the anthocyanin nucleus results in reduced stability.…”
Section: Effect Of Thawing Conditions On the Anthocyanin Profile Of Hsupporting
confidence: 75%
“…A similar reduction trend was seen as that observed for berries in frozen storage where C-3-G showed the highest reduction while the lowest reductions were noticed in peonidin 3-O-glucoside and pelargonidin 3-glucoside. This is supported by other studies that report that C-3-G is one of the most reactive ANCs during processing (Rommel et al, 1990;Boyles et al, 1993;Garcia-Viguera et al, 1998). Furthermore, Fleschhut et al (2006) reported that an increase in hydroxyl groups in the B-ring of the anthocyanin nucleus results in reduced stability.…”
Section: Effect Of Thawing Conditions On the Anthocyanin Profile Of Hsupporting
confidence: 75%
“…Furthermore, cyanidin-3-glucosylrutinoside was the most abundant anthocyanin found in the cherry wine, followed by cyanidin-3-rutinoside and cyanidin-3-glucoside, as indicated earlier (16,18,19). The raspberry wine had the highest concentration of cyanidin-3-sophoroside, followed by cyanidin-3-glucosylrutinoside and cya nidin-3-rutinoside, as noted previously (20). On the other hand, delphinidin glycoside derivatives including the most abundant delphinidin-3-rutinoside and the least abun dant delphinidin-3-glucoside, as well as cyanidin-3-rutinoside were identifi ed in the blackcurrant wine, as proposed earlier (17).…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 49%
“…Hence, it has been suggested that anthocyanin fi ngerprints of the wine relative to grapes might be the consequence of diff erent extraction rates of anthocyanins, or some degradation reactions that occur during winemaking. For example, the instability of cyanidin-3-glucoside during fermentation observed in blackberry (15) and red raspberry wines (20) is considered to be responsible for the lower concen tration of this compound in the wines compared to the fruits. In addi tion, the pigment analysis of the strawberry wine conducted earlier showed a signifi cant decrease of anthocyanin content aft er fermentation, where only 3-9 % of anthocyanins present in fruits were retained, as well as their progressive decrease throughout the storage (40).…”
Section: Individual Phenolic Compounds Of Fruit Winesmentioning
confidence: 99%
See 2 more Smart Citations